Pemikiran adab ketatanegaraan kesultanan Melayu - Jelani Harun (Dewan Bahasa dan Pustaka, 2003)
History of Malay sultanates in the classical Malay literatures
Includes bibliographical references (p. 405-414) and index
Keywords: Malay literature; Sultans; Monarchy